Association Between Sleep and Cognition of Older Adults in Rural Areas: A Cross-Sectional Study - Wenjia Meng MPH; Tianlin Gao PhD; Yang Zhong MPH; Ling Ge PhD (SAGE Publishing, 2023)
Sleep is an essential physiological function for everyone. Limited evidence existed on the associations between multi-factor sleep patterns and cognition among older adults in rural areas. Aimed to assess that, We conducted a cross-sectional study on the living habits and cognitive status in rural areas of Qingdao and 1167 participants aged 65 to 96 years answered the questionnaire. The result showed that poor sleep quality, high sleep disturbance, daytime dysfunction, and hypnotic drug-dominated sleep patterns were related to the cognitive function, and there was no obviously associations between good sleep duration and cognition. In order to solve the sleep problems and preserve cognitive function, support and protection of physical and mental health should be the priority of government policies in helping older adults' group in rural areas.